Soil macrofauna as indicators of soil quality in improved (silvo) pastoral systems in the tropics - Vázquez, Eduardo; Teutscherova, Nikola; Chagüezá, Yamileth; Botero, César; Benito, Marta; Gutiérrez Solís, Jhon Freddy; Sotelo Cabrera, Mauricio Efren; Arango, Jacobo; Pulleman, Mirjam Margreet (International Center for Tropical Agriculture, 2017)
Silvopastoral systems are environmentally and economically beneficial alternative to cattle pastures formed by single grass species. The incorporation of trees, especially legumes, in pastures has several positive effects on soil properties and nutrient cycling while creating more favorable microclimate for the animals and increasing productivity. Soil macrofauna, the key element in soil food web regulating ecosystem services, has a direct effect on soil aeration and water movement due to the system of burrows and galleries, and on soil organic matter fragmentation. The legumes or legume-trees inclusion in the pastures will lead to improved nutrient cycling and increased biological activity resulting in increased accumulation of organic matter and improved soil physical properties within the silvopastoral system.